Freshgraduate Motivation of Stikes Yarsi Mataram as Careworkers To Japan Through The Kaigho Fukushi-Shi Peer Support System - Putri Rusiana, Harlina; Istianah; Lalu Amri Yasir; Dewi Nur Sukma Purqoti (Universitas STRADA Indonesia, 2024)
The increasing number of nursing graduates with limited employment opportunities is a problem in almost all regions in Indonesia. Many work as voluntary nurses with salaries far below the regional minimum wage. Meanwhile, in Japan, the need for nurses as Kaigo Fukushi-shi (Caregiver) is very high. Through the Indonesia-Japan Economic Partnership Agreement (IJ-EPA) an agreement is made to send 1,000 careworkers every year. However, it only succeeded in sending 826 people in a span of 3 years through the G to G program. This study aims to measure the level of differences in the motivation of new graduates of STIKES YARSI Mataram before and after receiving assistance through the Kaigho Fukushi-shi Peer Support System from Alumni. The method used in this research is the Quasy Experiment without a control group with a total sample of 25 people. Obtained a p-value of 0.000 with a motivation value at the positive mean rank of all participants. It can be concluded that there is an influence from the Kaigho Fukushi-shi Peer Support System of the Alumni on the motivation of new graduates to work in Japan. Through this research, it contributes to the institution to be ready to use its graduates to gain experience working in Japan.